2015
DOI: 10.15557/jou.2015.0006
|View full text |Cite
|
Sign up to set email alerts
|

Enthesopathies and enthesitis. Part 1. Etiopathogenesis

Abstract: The pathologies of tendon and ligament attachments are called enthesopathies. One of its types is enthesitis which is a characteristic sign of peripheral spondyloarthropathy. Clinical diagnosis of enthesitis is based on rather non-specific clinical signs and results of laboratory tests. Imaging examinations are highly promising. Numerous publications prove that enthesitis can be differentiated from other enthesopathic processes in an ultrasound examination or magnetic resonance imaging. However, some reports i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 30 publications
2
28
0
13
Order By: Relevance
“…According to the theories on the etiopathogenesis of SpA ( 1 ) , US and MRI examinations confirmed that the inflammatory process may begin beyond entheses, i.e. in the synovium of the neighboring bursa (bursitis) where it is triggered (according to the mechanical theory) by enthesis microdamage ( fig.…”
Section: Bursitis Rather Than Enthesitis?mentioning
confidence: 93%
See 2 more Smart Citations
“…According to the theories on the etiopathogenesis of SpA ( 1 ) , US and MRI examinations confirmed that the inflammatory process may begin beyond entheses, i.e. in the synovium of the neighboring bursa (bursitis) where it is triggered (according to the mechanical theory) by enthesis microdamage ( fig.…”
Section: Bursitis Rather Than Enthesitis?mentioning
confidence: 93%
“…8 ), in the synovium of the tendon sheath (tenosynovitis, tendovaginitis) or in the peritendineum (according to the functional enthesis theory) as a response to a strain, e.g. pressing the tibialis posterior muscle on the medial malleolus ( 1 , 25 ) ( Fig. 9 ).…”
Section: Bursitis Rather Than Enthesitis?mentioning
confidence: 99%
See 1 more Smart Citation
“…Although enthesitis has traditionally been viewed as a focal abnormality, the inflammatory reaction intrinsic to enthesitis may be quite extensive [1]. In the clinical practice, the diagnosis of enthesitis is based on clinical examination, including interview (pain at the site of an enthesis that subsides following physical exercise) and observing pain in an enthesis upon compression [2]. Ultrasound and magnetic resonance image (RMI) are more direct ways to assess enthesitis although less feasible.…”
Section: Introductionmentioning
confidence: 99%
“…• Specific Indications for MRI in Children with JIA (►Figs. [22][23][24][25][26][27][28] • Evaluation of inflammatory changes in peripheral joints, tendon sheaths, and bursae. In the early phase of inflammation, exudate fluid, thickening, and postcontrast enhancement of the synovial membrane (representing synovitis, tenosynovitis, bursitis) are seen.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%